Vehicle collision with RC structures: A state-of-the-art review. (October 2022) - Xu, Xiuchen; Zhang, Hongchao; Du, Xiaobo; Liu, Qiang
Abstract: The paper reviews the state-of-art in the studies of RC structures subjected to vehicle collision. Failure modes, influencing factors and impact force response of different RC structures (conventional and reinforced) impacted by vehicular collision are analyzed, which is divided into three parts, that is, (i) Normal vehicle impact on bridge substructure; (ii) Over-high vehicle impact on bridge superstructure (main beam); (iii) Vehicle collision of crash barriers. The current techniques for studying vehicle-RC structure collision, i.e., numerical, experimental, and analytical techniques, are highlighted. In particular, the various numerical methods and laboratory tests are concluded and compared. Due to the inherent brittleness of concrete materials, local or overall failure often occurs when subjected to vehicular impact loading. The researchers changed the failure mode of the original RC structure by applying corresponding reinforcement to the exterior and interior of the RC structure, which could effectively mitigate the damage caused by the vehicle impact. Based on previous experimental, analytical, and simulation studies, the influences of structural factors and reinforcement materials on the impact resistance and failure response under three different impact modes are reviewed. The perspective and conclusions of this paper may provide some enlightenment of future work to the further improve the impact resistant design of RC structures.